Graphene Oxide and Its Inorganic Composites: Fabrication and Electrorheological Response - Dong, Yu Zhen (Materials (Basel), 2019)
Composite particles associated with graphene oxide (GO) and inorganic materials provide the synergistic properties of an appropriate electrical conductivity of GO with the good dielectric characteristics of inorganic materials, making them attractive candidates for electrorheological (ER) materials. This review paper focuses on the fabrication mechanisms of GO/inorganic composites and their ER response when suspended in a non-conducting medium, including steady shear flow curves, dynamic yield stress, On-Off tests, and dynamic oscillation analysis. Furthermore, the morphologies of these composites, dielectric properties, and sedimentation of the ER fluids are covered.